PENGEMBANGAN GAME INTERAKTIF GABATA BERBASIS KEARIFAN LOKAL KUDUS - Veronica; Fira Fatimatuz Zahra; Dwipa Ringi I Gusti; Rani Setiawaty (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This research focuses on creating a learning tool in the shape of an interactive game named GABATA (Gembira Tanda Baca), inspired by the cultural heritage of Kudus, to help second-grade elementary students grasp punctuation in their Indonesian language education. The motivation for this study stems from the inadequate comprehension of punctuation among students and the scarcity of interactive and relevant educational resources. The approach taken in this research was based on the Research and Development (RandD) framework, employing the ADDIE model, which encompasses analysis, design, development, implementation, and evaluation stages. The participants consisted of second-grade learners from SD Negeri 3 Barongan Kudus, along with validators including media specialists, subject matter experts, and linguists. Information was gathered through various questionnaires for validation and feedback from both teachers and students to evaluate the suitability and usability of the educational tool. The findings revealed that the GABATA media received a feasibility rating of 85. 58% from media specialists and 82. 69% from subject matter specialists, both considered very suitable. Additionally, the results from the practicality assessment showed a teacher feedback score of 96. 88%, while student feedback varied between 92. 5% and 100%, which is categorized as very practical. These results suggest that the GABATA interactive game, rooted in the cultural wisdom of Kudus, is highly appropriate and effective as an educational resource for teaching punctuation to elementary students..